The philosophy of being and possible in the Celebratory Theatre “ The Festive Theatre - HENNI , Karima (Journal of Social Sciences and Humanities, 2025)
The Celebratory Theatre ‘The Festive Theatre’ is different to the traditional /aristian theatre. It is part of a broad and inclusive philosophical system called theatricalism. It was employed in the Arab theatre in response to the calls for originalism that Arab intellectuals called a book and two theatre directors after the June 1967 setback. It is an attempt to promote the Arab theatre and to make it independent from Western theatre traditions and culture and civilization. The Moroccan artist and the theatrical theater Abdulkareem Rasheed is considered to be apractice and a theory of the concept of theatrical theatre in the statements of the celebratory theatrical theatre group,which seeks to find originality and reveal the truth within the confines of the organism, which can challenge the reality, the partial to the kidney, the local to the cosmos and the provisions to the laws. To go beyond standing in what is an object to visualizing what is possible and likely to be done to the Arab theatre is to make its gratuity and the original imag, not borrowed from the Western version, its elegance and virginity in its commemorative philosophy, which is defined in its social customs and traditions and which reflects a culture thatis neutral to the culture of the other. So what's up with the theatre ? What is addedby the philosophy of the Moroccan celebratory theatre group in its statements to create an authentic theatre and what reality it wants is new, changing and civilized..